Soil nitrogen availability and microbial carbon use efficiency are dependent more on chemical fertilization than winter drought in a maize–soybean rotation system - Bao, Wenqing; He, Peng; Han, Lin; Wei, Xiaowei; Feng, Lei; Zhu, Jianqin; Wang, Jihua; Yang, Xuechen; Li, Lu-Jun (Frontiers in Microbiology, 2024)
Soil nitrogen (N) availability is one of the limiting factors of crop productivity, it is strongly influenced by global change and agricultural management practices. However, very few studies have assessed how winter drought affected soil N availability during the subsequent growing season under chemical fertilization. We conducted a field investigation with snow removal to simulate winter drought at a 6-year fertilization experiment in a Mollisol cropland in Northeast China, and we tested soil physicochemical properties, microbial characteristics, and N availability. Our results demonstrated that chemical fertilization significantly increased soil ammonium and total N availability by 42.9% and 90.3%, respectively; a combined winter drought and fertilization treatment had the highest soil N availability, at the end of the growing season. As the growing season continued, the variation in soil N availability was explained more by fertilization than by winter drought. Mantel test further indicated that soil Olsen-P content and microbial carbon use efficiency were significantly related to soil ammonium availability. Microbial community structure explained the largest fraction of the variation on soil nitrate availability. Microbial carbon use efficiency had the strongest correlation with soil N availability, followed by soil available C: P and bacteria: fungi ratio under winter drought and chemical fertilization. Overall, we clarified that despite the effect of winter drought on soil N availability was weak, it cannot be ignored. Our study also identified the important role of soil microorganisms in soil N transformations, even in seasonally snow-covered northern croplands.